Antonim Mutlak dalam Bahasa Jawa: Kajian Semantik Leksikal - Endang Sri Maruti; Bambang Eko Hari Cahyono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
The purpose of this study is to describe and classify absolute antonyms in Javanese. This research is a descriptive qualitative type. The data are in the form of words, phrases, clauses, and sentences containing absolute antonyms taken from Javanese textbooks and textbooks in elementary and high schools. Data collection techniques with documentation, listening, and record. The data were analyzed using the "agih" method with the substitution technique and the reflexive-introspective method. The results show that the meaning of contrast does not mean the known contrast, which has been taught in schools so far. Based on the meanings explained by experts, the meaning of antonyms is more complex, and the types of antonyms also vary. In absolute antonyms, several properties must be fulfilled, A and B are said to be absolute antonyms if A is negated, the meaning is the same as B, and vice versa if B is negated, the meaning is the same as A. This pattern can be used as a reference for teachers to teach contrasting meaning material, especially in absolute antonyms.